A qualitative investigation of schizophrenic dreams - Kumarapaapillai, Niranjula (Rhodes University, Faculty of Humanities, Department of Psychology, 1998)
This project attempts to articulate an understanding of the worlds of selected subjects suffering from schizophrenia, through their dreams. It proceeds from the implicit question of whether or not schizophrenic dreams reflect the schizophrenic worlds as literature defines, and tries to address some of the dream features which reflect the schizophrenic world. Five psychiatric inpatients suffering from schizophrenia were selected. The data gathered included the subjects' dreams and subsequent interviews for the purpose of clarification of the dreams. A phenomenological-hermeneutic methodology was deemed to be appropriate as it gave access to the richness of the dream experiences as well as the following dialogue between the data and literature. The results indicate that the subjects' dream worlds bear evidence to a fragmented state of ego which is to be expected to be found in schizophrenia. On the other hand some of these subjects' dreams also point to evolving health that is present in their world, at least on an intrapsychic level.
Keywords: Schizophrenia; Dreams -- Psychological aspects